2019
DOI: 10.1177/1465312519880558
|View full text |Cite
|
Sign up to set email alerts
|

What evidence exists for myofunctional therapy with prefabricated appliances? A systematic review with meta-analyses of randomised trials

Abstract: Objective: To assess the treatment efficacy/efficiency with prefabricated myofunctional appliances (PMA) for children with malocclusion. Data sources: Nine databases searched without limitations till July 2019. Data selection: Randomised trials comparing PMAs to functional appliance treatment or no treatment. Data extraction: Study selection, data extraction and risk of bias assessment were done in duplicate. Data synthesis: Random-effects meta-analyses of mean differences (MDs) or relative risks (RRs) with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
6
0
2
Order By: Relevance
“…In the early 1900s, in the field of orthodontic therapy, with the help of orofacial muscular training, Rogers introduced oro-myofunctional appliances (OMFA) to Introduction the patients with growing maldentition to correct the unusual pattern of deglutition, treating the myofunctional and/or myoskeletal problems [10], focusing on the normal swallowing and nasal breathing, improving the balance of oro-facial musculature, and to promote mandibular development [11].…”
Section: Origin and History Of Patakaramentioning
confidence: 99%
“…In the early 1900s, in the field of orthodontic therapy, with the help of orofacial muscular training, Rogers introduced oro-myofunctional appliances (OMFA) to Introduction the patients with growing maldentition to correct the unusual pattern of deglutition, treating the myofunctional and/or myoskeletal problems [10], focusing on the normal swallowing and nasal breathing, improving the balance of oro-facial musculature, and to promote mandibular development [11].…”
Section: Origin and History Of Patakaramentioning
confidence: 99%
“…Removable functional appliances (Activator, Fränkel-2, Twin Block, or Sander appliance) were used in 16 studies, while fixed functional appliances (Herbst, Forsus Fatigue Resistant Device, Mandibular Protraction Appliance-IV, Mandibular Anterior Repositioning Appliance, or X-Bow appliance) were used in 8 studies (with 4 studies using both removable and fixed appliances). One study [32] also included a prefabricated myofunctional appliance (Trainer 4 Kids), but this was omitted from the review, due to the different modus operandi [49]. One study [44] incorporated headgear to the Activator for anchorage reinforcement, while another study [31] also included a second phase treatment with braces after a first phase with Twin Block.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Frongia et al investigated masticatory muscle function in 17 patients with jaw deformities, and reported that masticatory muscle function was bilaterally unbalanced 7) . Myofunctional therapy has been shown to eliminate the functional pressure of the masticatory muscles from the mechanical environment in the maxillofacial region, promoting the healthy development not only of the dentition but also of the maxilla and mandible, and is now widely used [8][9][10] . Inoue et al found that osteocytes were activated in mice given a high masticatory load, generating new bone at entheses of the masticatory muscles, and therefore these muscles undoubtedly have a major effect on the bone dynamics of the mandible 11) .…”
Section: Introductionmentioning
confidence: 99%